Efectividad de fungicidas de contacto sobre phytophthora infestans (Mont.) de bary en papa - Rodriguez, F.=700 1 Muiño, B.L.; Almandoz, J.; Porras, A.
(Es, En)
Ilus., 10 ref.
Keywords: FUNGICIDAS; METALAXIL; MANCOZEB; CLOROTALONIL; CONTROL QUIMICO; PHYTOPHTHORA INFESTANS; SOLANUM TUBEROSUM; CUBA